Functional Oxide Thin Films and Nanostructures: Growth, Properties, and Applications - Mele, Paolo; Kaneko, Satoru; Endo, Tamio (MDPI - Multidisciplinary Digital Publishing Institute, 2022)
This Special Issue of Coatings is entitled "Functional Oxide Thin Films and Nanostructures: Growth, Properties, and Applications". Recent materials nanotechnologies have created possibilities regarding the fabrication of oxide thin films at the nanometric level and other nanocomposites' fabrication. In parallel, recent measurement technologies can characterize their unique properties arising from the limited regions of surfaces and interfaces. This Special Issue provides an opportunity to share surface-related science and engineering topics on oxide thin films and nanocomposites in an interactive and interdisciplinary manner. The ultimate goal is to elucidate the commonalities and differences between multilayer interfaces and nanocomposite grain boundaries. This Special Issue is as an effort to bridge the gap between materials science and the applications of oxide thin films and nanostructures. The topics covered in this Special Issue range from nanoparticles to thin films, heterostructures, and homojunctions and are related to various aspects of oxide materials' preparation, characterization, and applications.